Stratified analysis of 800 Asian patients after robot‐assisted radical prostatectomy with a median 64 months of follow up. (8th July 2016) - Abdel Raheem, Ali; Kim, Dae Keun; Santok, Glen Denmer; Alabdulaali, Ibrahim; Chung, Byung Ha; Choi, Young Deuk; Rha, Koon Ho
Abstract : Objective: To report the 5‐year oncological outcomes of robot‐assisted radical prostatectomy from the largest series ever reported from Asia. Methods: A retrospective analysis of 800 Asian patients who were treated with robot‐assisted radical prostatectomy from July 2005 to May 2010 in the Department of Urology and Urological Science Institute, Yonsei University College of Medicine, Seoul, Korea was carried out. The primary end‐point was to evaluate the biochemical recurrence. The secondary end‐point was to show the biochemical recurrence‐free survival, metastasis‐free survival and cancer‐specific survival. Results: A total of 197 (24.65%), 218 (27.3%), and 385 (48.1%) patients were classified as low‐, intermediate‐ and high‐risk patients according to the D'Amico risk stratification risk criteria, respectively. The median follow‐up period was 64 months (interquartile range 28–71 months). The overall incidence of positive surgical margin was 36.6%. There was biochemical recurrence in 183 patients (22.9%), 38 patients (4.8%) developed distant metastasis and 24 patients (3%) died from prostate cancer. Actuarial biochemical recurrence‐free survival, metastasis‐free survival, and cancer‐specific survival rates at 5 years were 76.4%, 94.6% and 96.7%, respectively. Positive lymph node was associated with lower 5‐year biochemical recurrence‐free survival (9.1%), cancer‐specific survival (75.7%) and metastasis‐free survival (61.9%) rates ( P < 0.001). On multivariable analysis, among all the predictors, positive lymph node was the strongest predictor of biochemical recurrence, cancer‐specific survival and metastasis‐free survival ( P < 0.001). Conclusions: Herein we report the largest robot‐assisted radical prostatectomy series from Asia. Robot‐assisted radical prostatectomy is confirmed to be an oncologically safe procedure that is able to provide effective 5‐year cancer control, even in patients with high‐risk disease.